The Impact of COVID-19 Infection History on Oxygen Saturation in Elective Surgery Patients - Irwadi, Irwadi; Elfira, Yenni; Fatimah, Fatimah (GLOBAL HEALTH SCIENCE GROUP, 2023)
Coronavirus Disease (COVID-19) infection can cause complications in the respiratory system including oxygen saturation, this condition can affect the condition of post-surgery patients. In patients who will undergo surgery, optimal oxygen saturation is very important in maintaining hemodynamic stability and success in anesthesia and patient recovery. The purpose of this study was to determine the impact of a history of COVID-19 infection on oxygen saturation in elective surgical patients. The design of this study was an observational analytical study with a cross-sectional approach. The sample size was 76 people consisting of 38 groups with a history of COVID-19 and 38 groups with a history of COVID-19. The sampling method used a purposive sampling technique with respondent criteria that had been determined according to the inclusion and exclusion criteria. The results of the Independent Sample t-test showed a significant difference in decreased oxygen saturation in patients with a history of COVID-19 compared to patients without a history of COVID-19 with the results (p <α = 0.05). It can be concluded that a history of COVID-19 infection has an impact on decreased oxygen saturation in elective surgical patients. These findings suggest the importance of careful preoperative evaluation and more intensive oxygenation monitoring in patients with a history of COVID-19 infection to minimize the risk of intraoperative and postoperative complications.